On (J, p_n) summability of fourier series - Chandra, Satish (Tamkang Journal of Mathematics, 2001)
In this paper we prove the following two theorems for | J, p_n | summability of fourier series, which generalizes many previous result: Theorem 1. If Φ (t) = _t^π φ (u)u du = o { p (1- 1t ) } (t → 0) then the Fourier series for t = x is summable (J, p_n) to sum s . Theorem 2. If G(t) = _t^π g(u)u du = o { p(1-1t) } (t → 0) then the differentiated Fourier series is summable (J, p_n) to the value C .